Autonomous English learning: Teachers’ and students’ perceptions - Khotimah, Khusnul; Widiati, Utami; Mustofa, Mutmainnah; Ubaidillah, M. Faruq (Indonesian Journal of Applied Linguistics, 2019)
This study aims at investigating teachers’ and students’perceptions of autonomous learning in English language teaching and to what extent the teachers foster students’ autonomous learning. A set of questionnaire was distributed to 30 English teachers and 283 third-year secondary school students in the provincial part of Indonesia. The participants in this study were randomly selected. Furthermore, to obtain the supplementary data, an interview was conducted to two students from each school. The findings indicate that albeit positive tenets on autonomous learning were held by both teachers and students, they still had inadequate understandings of what autonomous learning concepts are. In terms of exposing students to autonomous learning, the teachers possess highly-driven endeavor. This study ends with suggestions for teachers and teacher education programs.